Enhancing Bilateral Ties: Analyzing the Multidimensional Cooperation between Indonesia and South Korea under the NSP Plus Framework - Wijaya, Bagaskara Sagita; Rimapradesi, Yulia; Awalia, Hunna Khawaiga; Mubarok, Sofi (Jurnal Hubungan Internasional, 2025)
The New Southern Policy (NSP) Plus, an initiative by South Korea to deepen its ties with the Association of Southeast Asian Nations (ASEAN), presents a unique opportunity for enhanced bilateral cooperation and development, particularly with Indonesia. This research delves into the dynamics and potential of this intensified partnership, focusing on its implications for domestic and international economic and social empowerment. This study is anchored in the neoliberal institutional theory with the Keynesianism perspective within international relations, offering a nuanced perspective on international cooperation’s mechanisms and multidimensional outcomes. Employing a qualitative research method and descriptive analysis, this study examined the complementary aspects of Indonesia and South Korea’s economies and how these synergies can elevate the NSP Plus initiative from a bilateral framework to a more expansive model of international cooperation. This research posits that the mutual benefits derived from this partnership are pivotal in fostering closer ties and can potentially be replicated in other areas of international collaboration. A significant aspect of this study is the exploration of the government’s role as a policy facilitator and the active involvement of the private sector and broader community in these cooperative efforts. This multi-stakeholder approach is critical in understanding the dynamics of international cooperation and its impact on societal elements. Furthermore, this research applied the Keynesianism concept of the five-multiplier effect on economic growth to analyze how the NSP Plus policy can bolster domestic development cycles. It includes job creation, market expansion, and investment market growth, all facilitated by the private sector’s engagement. The study aims to comprehensively understand the NSP Plus initiative’s potential in strengthening Indonesia-South Korea relations and its broader implications for regional economic development and international cooperation.